Consumption of fruits and vegetables and probabilistic assessment of the cumulative acute exposure to organophosphorus and carbamate pesticides of schoolchildren in Slovenia. Issue 3 (20th May 2015) - Blaznik, Urška; Yngve, Agneta; Eržen, Ivan; Hlastan Ribič, Cirila
Abstract: Objective: Adequate consumption of fruits and vegetables is a part of recommendations for a healthy diet. The aim of the present study was to assess acute cumulative dietary exposure to organophosphorus and carbamate pesticides via fruit and vegetable consumption by the population of schoolchildren aged 11–12 years and the level of risk for their health. Design: Cumulative probabilistic risk assessment methodology with the index compound approach was applied. Setting: Slovenia, primary schools. Subjects: Schoolchildren ( n 1145) from thirty-one primary schools in Slovenia. Children were part of the PRO GREENS study 2009/10 which assessed 11-year-olds' consumption of fruit and vegetables in ten European countries. Results: The cumulative acute exposure amounted to 8·3 (95 % CI 7·7, 10·6) % of the acute reference dose (ARfD) for acephate as index compound (100 µg/kg body weight per d) at the 99·9th percentile for daily intake and to 4·5 (95 % CI 3·5, 4·7) % of the ARfD at the 99·9th percentile for intakes during school time and at lunch. Apples, bananas, oranges and lettuce contributed most to the total acute pesticides intake. Conclusions: The estimations showed that acute dietary exposure to organophosphorus and carbamate pesticides is not a health concern for schoolchildren with the assessed dietary patterns of fruit and vegetable consumption.